Analisis Manajemen SDM Unit Intel Bidang Sosial Budaya Polres Lampung Tengah - Widodo, Wahyu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2020)
Human resources (HR) is a key element in an organization that functions as a driver and implementation of the organization's vision and mission. Management of resources in an organization determines the organization's development and improvement in order to achieve organizational goals. A holistic management ledge is needed to build and manage the organization's resources so that it can be of maximum benefit to the organization's progress. This research was conducted to analyze the HR management at the Intel Social and Cultural Unit of the Central Lampung District Police which was presented through a descriptive qualitative analysis. This research refers to the concept of resource management regarding management functions as an effort to improve the quality of organizational services through planning, organizing, actuating and controlling. This research found that in an effort to manage human resources at the Intel Social and Cultural Unit of the Central Lampung District Police, it was done even though it could not yet run perfectly. Sumber daya manusia (SDM) merupakan elemen kunci dalam suatu organisasi yang berfungsi sebagai penggerak dan implementasi visi dan misi organisasi. Pengelolaan sumber daya dalam suatu organisasi menentukan perekembangan dan peningkatan organisasi tersebut dalam rangka mencapai tujuan organisasi. Diperlukan langkan pengelolaan yang holistik untuk membangun dan mengelola sumber daya organisasi yang dimiliki sehingga dapat bermanfaat secara maksimal bagi kemajuan organisasi. Penelitian ini dilakukan untuk menganalisis manajemen SDM pada unit Intel Bidang Sosial dan Budaya Polres Lampung Tengah yang dipaparkan melalui analisis deskriptif kualitatif. Penelitian ini mengacu pada konsep manajemen sumber daya mengenai fungsi manajemen sebagai upaya untuk meningkatkan kualitas pelayanan organisasi melalui planning, organizing, actuating dan controlling. Penelitian ini menemukan bahwa dalam upaya manajemen SDM pada unit Intel Bidang Sosial dan Budaya Polres Lampung Tengah sudah dilakukan meskipun belum dapat berjalan dengan sempurna.